Televizijos reklamos elementų vertinimo ir reklamuojamų prekių pirkimo tendencijos Lietuvoje krizės sąlygomis - Sirtautas, Vytautas V. V.; Sirtautienė, Daiva (Information & Media, 2012)
Straipsnyje aprašomi trijų pjūvių, atliktų ikikriziniu (2007 m.) ir krizės (2009 m., 2011 m.) laikotarpiais, rezultatai siekiant išsiaiškinti, kokia televizijos reklama yra efektyvi krizės metu. Analizuojami ir lyginami tiek bendrieji, tiek skirtingų kartų̃ (paauglių, tėvų ir senelių) duomenys – tikrinama, ar ekonominės krizės sąlygomis kinta auditorijos požiūris į atskirus televizijos reklamos elementus (humorą, dalykiškumą, įvairias prekių kategorijas, reklamavimo aplinką, veikėjus), nuostatos pirkti reklamuojamas prekes, taip pat materialinės padėties pajautos bei gyvensenos vertinimo tendencijos Lietuvoje.Reikšminiai žodžiai: ekonominė krizė, reklama, TV auditorija, kartos, Lietuva.The Tendencies of TV Advertisement Elements Evaluation and Advertised Items Purchase in Lithuania in Conditions of Economic CrisisVytautas V. Sirtautas, Daiva SirtautienėSummaryThe article discusses results of three studies conducted in the pre-crisis period (2007) and during crisis (2009, 2011). Both general and segmented data on three generations (teenagers, parents, grandparents) are analyzed and compared. The aim of this research was to ascertain the alterations in the evaluation of TV advertisements and in the attitude towards purchasing the advertised items under the circumstances of economic crisis in Lithuania. It has been analyzed whether in conditions of crisis the audience’s attitude towards separate advertisement elements (humor, efficiency, various item categories, advertising environment, characters) changes, as well as the current material state and lifestyle estimation tendencies in Lithuania.Research hypotheses: under the circumstances of crisis, the audience’s attitude towards different advertisement elements does not change significantly (H1); the tendencies of advertised items purchase are influenced negatively (H2).The first hypothesis (H1) was not confirmed. The data revealed an opposite result: from 2007 till 2011, several tendencies of advertisements’ element evaluation changes were established, the most pronounced being the decreasing audience that prioritize items advertised with humor, and the increasing preference of the businesslike style; the number of people preferring businesslike and not recreational advertisements; also, when the main character is a specialist in the field and not a celebrity; the environment of the item testing laboratory and industrial advertising are more and more valued.The facts that confirm the second hypothesis (H2) were identified. Although consumers’ attitude towards purchasing hardly changed, the number of consumers with the attitude to buy an advertised item decreased and with the attitude not to buy the item increased.Keywords: economic crisis, advertising, TV audience, generations, Lithuania. 10.5pt; line-height: 115%; font-family: Calibri, sans-serif;">